The Islamic Models of Saving and Investment sebagai Suatu Tawaran atas Perilaku Impulse Buying pada Produk dan Jasa Taḥsīnīyāt - Ika Yunia Fauzia (Islamica: Jurnal Studi Keislaman, 2018)
The behavior of impulsive buying becomes common today, along with the rampant variety of marketing promotions carried out by business people. Many consumers make purchases impulsively after being attracted to several factors that drive this behavior. The purchases due to unplanned decisions often occur in products and services of taḥsīnīyāt. Actually there is nothing wrong with the behavior of impulsive buying if the consumers who do it have fulfilled the ḍarūrīyāt needs and have prepared their future needs. However, it becomes a problem if impulsive buying for products and services of taḥsīnīyāt precede the primary needs that have not been fulfilled properly. This research will try to provide a brief solution on how to limit the self from rughbah and shahwat of buying, by planning income for several financial posts. Here the author offers the concept of Islamic models of saving and investment which can also be interpreted as Islamic family wealth management. It is hoped that this research can provide a meaningful contribution to human development.